A Ni2P modified Ti4+ doped Fe2O3 photoanode for efficient solar water oxidation by promoting hole injection. Issue 32 (12th May 2017) - Bu, Qijing; Li, Shuo; Cao, Shuang; Zhao, Qidong; Chen, Yong; Wang, Dejun; Xie, Tengfeng
Abstract : Nickel phosphide (Ni2 P) was used as an excellent water oxidation cocatalyst for photoelectrochemical (PEC) water splitting, which could significantly promote the hole injection efficiency and suppress the back reaction of water oxidation over a Ti 4+ doped Fe2 O3 photoanode. Abstract : Nickel phosphide (Ni2 P) was used as an excellent water oxidation cocatalyst for photoelectrochemical (PEC) water splitting, which could significantly promote the hole injection efficiency and suppress the back reaction of water oxidation over a Ti 4+ doped Fe2 O3 photoanode.